LARANGAN MENIKAH BORU NINAMBORU MENURUT PERSPEKTIF HUKUM ISLAM (Studi Kasus di Kampung Binubu Baru Nagari Sontang Padang Gelugur Kabupaten Pasaman) - Martua Martua; Irma Suryani (Institut Agama Islam Negeri Batusangkar, 2022)
The main problem in this paper is the provisions on the prohibition of marrying boru ninamboru and the view of Islamic law on the prohibition of marrying boru ninamboru in the village of Binubu Baru, Nagari Sontang Cubadak, Pasaman Regency. The purpose of this study is to find out how the provisions on the prohibition of marrying boru ninamboru and analyzing how Islamic law views the prohibition of marrying boru ninamboru in the village of Binubu Baru Nagari Sontang Cubadak, Pasaman Regency. This type of research is this research is field research (field research). Data collection was carried out through interviews with respondents, namely traditional leaders, religious scholars and people who would commit the customary violation. After the data is obtained, the writer analyzes it descriptively qualitatively so that the data is understood. The location of this research is in Binubu Baru Village, Padang Gelugur District, Pasaman Regency. From the results of the study, it was found that the rules regarding the prohibition of marrying boru ninamboru were believed to exist by the people of Kampung Binubu Baru Nagari Sontang Cubadak, Pasaman Regency. This customary prohibition against marrying boru ninamboru has never happened because of the strong belief of the community in the prevailing customs and the sanctions that are so strong and strict. The provisions on the prohibition of marrying boru ninamboru in Kampung Binubu Baru have become rules that have existed in ancient times originating from ancestors, followed until now from generation to generation, these rules are not written but are firmly held by traditional leaders accompanied by sanctions. In the view of Islamic law that marriage to boru ninamboru is allowed and not prohibited in religion which has been explained in surah An-Nisa verses 22-23, for that customs regarding the prohibition of marrying boru ninamboru are included in 'urf fasid.